2019
DOI: 10.18388/pb.2019_267
|View full text |Cite
|
Sign up to set email alerts
|

Ludzka rybonukleaza Dicer – struktura i funkcje biologiczne

Abstract: Rybonukleaza Dicer jest znana przede wszystkim z kluczowej roli, jaką odgrywa w proce­sie biogenezy krótkich regulatorowych RNA: miRNA oraz siRNA. Badania prowadzone w ostatnich latach znacząco wzbogaciły wiedzę dotyczącą funkcji pełnionych przez Dicer. Wykazano, że Dicer jest zaangażowana w metabolizm zróżnicowanej puli RNA, m.in. tRNA i snoRNA, usuwanie potencjalnie cytotoksycznych cząsteczek RNA oraz utrzymywanie sta­bilności genomu. Co więcej, podczas apoptozy, w następstwie cięcia proteolitycznego przez k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Human Dicer (hDicer) consists of 1,922 amino acids (∼220 kDa) and comprises an amino (N)-terminal helicase domain, a domain of unknown function (DUF283), a Platform domain, Piwi-Argonaute-Zwille (PAZ) domain, a Connector helix, two RNase III domains (IIIa and IIIb) and a dsRNA-binding domain (dsRBD) ( Figure 1A ) [6]. The Platform-PAZ-Connector helix fragment is often called “the PAZ cassette” [7] or “the PPC cassette” [8]. The three-dimensional structure of hDicer resembles the letter L ( Figure 1B ) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Dicer (hDicer) consists of 1,922 amino acids (∼220 kDa) and comprises an amino (N)-terminal helicase domain, a domain of unknown function (DUF283), a Platform domain, Piwi-Argonaute-Zwille (PAZ) domain, a Connector helix, two RNase III domains (IIIa and IIIb) and a dsRNA-binding domain (dsRBD) ( Figure 1A ) [6]. The Platform-PAZ-Connector helix fragment is often called “the PAZ cassette” [7] or “the PPC cassette” [8]. The three-dimensional structure of hDicer resembles the letter L ( Figure 1B ) [9].…”
Section: Introductionmentioning
confidence: 99%
“…1a ) [6]. The Platform-PAZ-Connector helix fragment is often called “the PAZ cassette” [7] or “the PPC cassette” [8]. The three-dimensional structure of hDicer resembles the letter L ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…One well-known mechanism is that long double-stranded RNAs (dsRNAs) derived from the virus in infected cells induce RNA interference (RNAi) to specifically remove viral RNAs [ 34 , 35 ]. Dicer, a member of the RNase III family, cleaves these dsRNAs into virus-derived small interfering RNAs (viRNAs), which are loaded into Argonaute (AGO) proteins to form the RNA-induced silencing complex (RISC) and thereby silencing viral RNAs [ 36 , 37 , 38 , 39 ]. Recent studies have identified a novel mechanism of virus–host interaction, which is conserved across animals and mediated through 3′ tailing of viral RNAs [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%